2016
DOI: 10.1073/pnas.1611494113
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae biofilm growth program and architecture revealed by single-cell live imaging

Abstract: Biofilms are surface-associated bacterial communities that are crucial in nature and during infection. Despite extensive work to identify biofilm components and to discover how they are regulated, little is known about biofilm structure at the level of individual cells. Here, we use state-of-the-art microscopy techniques to enable live singlecell resolution imaging of a Vibrio cholerae biofilm as it develops from one single founder cell to a mature biofilm of 10,000 cells, and to discover the forces underpinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
210
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 167 publications
(232 citation statements)
references
References 44 publications
10
210
1
1
Order By: Relevance
“…However, in many cases, bacteria can develop three-dimensional multicellular structures [4,10,47]. Extending our work to three dimensions is nontrivial as many new features such as the cell-surface interaction resulting from symmetric or asymmetric adhesion of anisotropic bacteria with the substrate might also influence the structure of a colony [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, in many cases, bacteria can develop three-dimensional multicellular structures [4,10,47]. Extending our work to three dimensions is nontrivial as many new features such as the cell-surface interaction resulting from symmetric or asymmetric adhesion of anisotropic bacteria with the substrate might also influence the structure of a colony [48].…”
Section: Discussionmentioning
confidence: 99%
“…They crosslink together and make protective layer in which bacteria lives with slow metabolic rate (Mann et al ; Alhede et al ; Yan et al . ; Jamal et al ). This protective barrier of biofilms offer strong resistance against antibiotics, host immune response, degrading enzymes etc (Stewart and Costerton ; Shahwany et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are mainly composed of~96-97% of water and extra polymeric substances (~3-4%) (EPS layer) which includes polysaccharides, proteins and nucleic acids (DNA and RNA). They crosslink together and make protective layer in which bacteria lives with slow metabolic rate (Mann et al 2009;Alhede et al 2011;Yan et al 2016;Jamal et al 2018). This protective barrier of biofilms offer strong resistance against antibiotics, host immune response, degrading enzymes etc (Stewart and Costerton 2001;Shahwany et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has often been assumed that the key driver of the observed architecture of biofilms in flow is bulk deformation or erosion of biofilm biomass [16,19,20]. Using single-cell live imaging [21,22], we recently observed that cells within biofilms in high shear tend to align with the direction of fluid flow [17]. However, despite the extensive environmental relevance of flow-biofilm interactions, it has been unclear to what extent flow-induced cellular reorientations contribute to overall microscopic biofilm structure and macroscopic biofilm shape.…”
Section: Introductionmentioning
confidence: 99%